Experimental Courses of Foreign Languages at the Department of Germanic Linguistics of the Adam Mickiewicz University at Poznań - Zabrocki, Ludwik (Glottodidactica, 1966)
Experimental Courses of Foreign Languages at the Department of Germanic Linguistics of the Adam Mickiewicz University at Poznań